2011
DOI: 10.1136/annrheumdis-2011-200275
|View full text |Cite
|
Sign up to set email alerts
|

Novel identification of the IRF7 region as an anticentromere autoantibody propensity locus in systemic sclerosis

Abstract: Objective Systemic sclerosis (SSc) and systemic lupus erythematosus (SLE) are related chronic autoimmune diseases of complex aetiology in which the interferon (IFN) pathway plays a key role. Recent studies have reported an association between IRF7 and SLE which confers a risk to autoantibody production. A study was undertaken to investigate whether the IRF7 genomic region is also involved in susceptibility to SSc and the main clinical features. Methods Two case-control sets of Caucasian origin from the USA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Furthermore, recent genetic studies have established IRF7 as a susceptibility locus in SLE (7780). Similarly, our group recently reported that a functional variant in the IRF7 exonic region, rs1131665 was associated with SSc (35). These findings support that IRF7 may represent a common risk factor for systemic autoimmune disease processes, including SSc.…”
Section: Interferon Regulatory Factors and Sscmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, recent genetic studies have established IRF7 as a susceptibility locus in SLE (7780). Similarly, our group recently reported that a functional variant in the IRF7 exonic region, rs1131665 was associated with SSc (35). These findings support that IRF7 may represent a common risk factor for systemic autoimmune disease processes, including SSc.…”
Section: Interferon Regulatory Factors and Sscmentioning
confidence: 53%
“…These studies independently replicated genetic risk factors such as STAT4 (2426), BLK (2730), BANK1 (31, 32), Interferon regulatory factor ( IRF ) -5 (33, 34), IRF-7 , and -8 (3538), and the T cell receptor zeta-chain ( CD247 ) (26) which are involved in innate and adaptive immune system.…”
Section: Innate Immunity and Sscmentioning
confidence: 86%
“…Carmona et al, found an additional association of another IRF gene, IRF7, with the presence of ACA in SSc patients [41]. Interestingly, IRF7 also represents a risk factor for SLE autoantibody production [42,43].…”
Section: Non-hlamentioning
confidence: 96%
“…However, the real implication of IRF7 in the modulation, the reproducibility of these eQTL findings in SSc patients and the functional mechanisms that connect all the previously mentioned processes require experimental confirmation. Furthermore, Carmona et al suggested that the association in IRF7 may be due to a different variant, a non-synonymous SNP (rs1131665), although the dependence between both signals is not clear [41]. Thus, additional efforts and research may shed light on the actual relevance of this locus and its structure in SSc.…”
Section: Exploring the Functional Roles Of Genetic Susceptibility Locimentioning
confidence: 97%
See 1 more Smart Citation